Exercise Prescription - Older Adults - Axtell, Robert; Robertson, M. I. (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

Muscular Strength Assessment - Axtell, Robert (ACSM's Exercise Testing and Prescription, 2023)
Keywords: dept.hms

The impact of an 8-week wellness peer coaching program on physical activity among college students: 1338 - Peacock, Jessica; Yan, Zi; Bowling, April; Benes, Sarah (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Marathon and ultra-endurance performance - Lunn, William R. (Medicine & Science in Sports & Exercise, 2023)
Keywords: dept.hms; peer-reviewed

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Prevalence of physical activity, sleep, and screen-time in youth before and during the covid-19 pandemic: 1735 - Rupp, Kristie; Friel, Ciaran P. (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

Evaluating the Usability of the Wellness School Assessment Tool Whole School, Whole Community, Whole Child (WellSAT WSCC): A School Wellness Policy Assessment Tool - Connolly, K.; Koslouski, J.B.; Chafouleas, S.M.; Schwartz, M.B.; Edmondson, B.; Briesch, A.M. (Journal of School Health, 2023)
BACKGROUND: Adoption of the Whole School, Whole Community, Whole Child (WSCC) model has been slowed by a lack of available tools to support implementation. The Wellness School Assessment Tool (WellSAT) WSCC is an online assessment tool that allows schools to evaluate the alignment of their policies with the WSCC model. This study assesses the usability of the WellSAT WSCC. METHODS: Using a convergent mixed methods design, we collected qualitative and quantitative data from 5 school-based participants with roles in development and evaluation of policy. Participants explored the platform while engaging in a think-aloud procedure and scored a sample policy using the platform. They also completed the System Usability Scale and responded to open-ended questions about the usability of the platform. RESULTS: Participants rated the WellSAT WSCC as an above-average user experience, but data suggested several areas for improvement, including improved instructions, enhanced visual design of the platform, and guidance for subsequent policy changes. CONCLUSION: The WellSAT WSCC provides an above-average user experience but can be improved to increase user experience. These improvements increase the potential for greater use to facilitate integration of the WSCC model into school policy. © 2023, American School Health Association.
Keywords: WSCC model; WellSAT WSCC; dept.hms; peer-reviewed; school health; school policy; whole child

Do maturation, anthropometrics and leg muscle qualities influence repeated change of direction performance in adolescent boys and girls? - Giuriato, M.; Pellino, V.C.; Lovecchio, N.; Codella, R.; Vandoni, M.; Talpey, S. (Biology of Sport, 2023)
The ability to change direction rapidly is a key fitness quality especially in invasive sports where young players perform approximately 300 changes of direction in a game. There is currently limited understanding of how anthropometric characteristics and maturation status influence change of direction ability in adolescent. Therefore, the purpose of this investigation is to assess the influence of anthropometrics and maturation status on change of direction ability in young people. The study involved 706 adolescents (367 girls) aged 14-19-year-old attending the same high school in Northern Italy. Stature, body mass, seated height and leg length were measured to determine the anthropometrics and maturation status of the participants. Repeated change of direction ability (10 × 5 m shuttle run test), lower limb power and muscle strength were evaluated using field tests from the Eurofit test battery. Maturity offset was calculated separately for boys and girls, in accord with the equation proposed by Mirwald. Preliminary analysis with 10 × 5 m as a dependent variable and sex and PHV as a fixed factor, suggests a significant difference between sex (p < 0.001; d = 0.35) but not with PHV (p = 0.986; d = 0.000) and interaction PHV × sex (p = 0.836; d = 0.000). Our results suggested that repeated change of direction performance was influenced by anthropometrics, maturation and muscle qualities in adolescent boys and girls. © 2023 Institute of Sport. All rights reserved.
Keywords: Adolescent; Change of Direction; Eurofit Test; Peak Height Velocity; Speed; dept.hms; peer-reviewed

Physical Activity, Sleep, and Screen Time in Children and Adolescents Before and During the COVID-19 Pandemic: An Analysis of the 2019-2020 National Survey of Children’s Health - Friel, C.P.; Diaz, K.M.; Rupp, K. (American Journal of Health Promotion, 2023)
The COVID-19 pandemic led to unprecedented changes in people’s lifestyles across the United States, but the extent to which the pandemic affected health behaviors of children and adolescents (i.e., physical activity, screen-time, and sleep) is not well understood. These behaviors hold particular significance because of their association with health outcomes. Purpose: The purpose of this study was to examine whether engagement in health behaviors changed from pre-pandemic (2019) to during the pandemic (2020). Methods: The combined 2019-2020 National Survey of Children’s Health (NSCH) was used to inform this study. The NSCH is an annual survey designed to provide national estimates of key indicators of childhood health and well-being. Physical activity (number of days/week with >60 min of activity), screen-time (hours/day of TV viewing and computer use), and sleep (hours/day) were assessed by parental report. Adjusted binomial and multinomial logistic regression models were used to determine the association between survey year and health behaviors. Results: Children and adolescents were 36% more likely to be physically inactive in 2020 compared to 2019. Additionally, children and adolescents were 14% more likely to meet sleep guidelines and 39% less likely to meet screen-time guidelines in 2020 compared to 2019, independent of age, sex, race/ethnicity, and poverty level. Children (6-13 year) and adolescents (14-17 years) were 10% and 15% less likely to get below the recommended amount of sleep in 2020 compared to 2019, respectively. Conclusion: Prevalence of meeting sleep guidelines increased among children and adolescents in 2020 but decreased for physical activity and screen-time. Initiatives targeting activity and screen-time may be urgently needed. Whether rates of these health behaviors return to pre-pandemic levels over the next few years should be closely assessed. © The Author(s) 2023.
Keywords: adolescents; children; dept.hms; health behaviors; peer-reviewed; physical activity; screen time; sedentary behavior; sleep

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
Keywords: dept.hms; peer-reviewed

Exertional heat illness: adoption of policies and influencing contextual factors as reported by athletic administrators - Scarneo-Miller, Samantha E.; Adams, William M.; Coleman, Kelly A.; Lopez, Rebecca M. (Sports Health, 2023)
Background:Little is known about the adoption by athletic administrators (AAs) of exertional heat illness (EHI) policies, and the corresponding facilitators and barriers of such policies within high school athletics. This study describes the adoption of comprehensive EHI policies by high school AAs and explores factors influencing EHI policy adoption.Hypothesis:We hypothesized that <50% of AAs would report adoption of an EHI policy, and that the most common facilitator would be access to an athletic trainer (AT), whereas the most common barrier would be financial limitations.Study Design:Cross-sectional.Level of Evidence:Level 4.Methods:A total of 466 AAs (82.4% male; age, 48 ± 9 years) completed a validated online survey to assess EHI prevention and treatment policy adoption (11 components), as well as facilitators and barriers to policy implementation. Access to athletic training services was ascertained by matching the participants? zip codes with the Athletic Training Locations and Services Project. Policy adoption, facilitators, and barriers data are presented as summary statistics (proportions, interquartile range (IQR)). A Welch t test evaluated the association between access to athletic training services and EHI policy adoption.Results:Of the AAs surveyed, 77.9% (n = 363) reported adopting a written EHI policy. The median of EHI policy components adopted was 5 (IQR = 1,7), with only 5.6% (n = 26) of AAs reporting adoption of all policy components. AAs who had access to an AT (P = 0.04) were more likely to adopt a greater number of EHI-related policies, compared with those without access to an AT. An AT employed at the school was the most frequently reported facilitator (36.9%).Conclusion:Most AAs reported having written EHI policy components, and access to an AT resulted in a more comprehensive policy.Clinical Relevance:Employment of an AT within high school athletics may serve as a vital component in facilitating the adoption of comprehensive EHI policies.
Keywords: dept.hms; peer-reviewed

An 8-week peer health coaching intervention among college students: a pilot randomized study - Yan, Zi; Peacock, Jessica; Cohen, Juliana F. W.; Kurdziel, Laura; Benes, Sarah; Oh, Seungbin; Bowling, April (Nutrients, 2023)
This study explored the effects of an 8-week peer coaching program on physical activity (PA), diet, sleep, social isolation, and mental health among college students in the United States. A total of 52 college students were recruited and randomized to the coaching (n = 28) or the control group (n = 24). The coaching group met with a trained peer health coach once a week for 8 weeks focusing on self-selected wellness domains. Coaching techniques included reflective listening, motivational interviews, and goal setting. The control group received a wellness handbook. PA, self-efficacy for eating healthy foods, quality of sleep, social isolation, positive affect and well-being, anxiety, and cognitive function were measured. No interaction effects between time and group were significant for the overall intervention group (all p > 0.05), while the main effects of group difference on moderate PA and total PA were significant (p < 0.05). Goal-specific analysis showed that, compared to the control group, those who had a PA goal significantly increased vigorous PA Metabolic Equivalent of Task (METs) (p < 0.05). The vigorous METs for the PA goal group increased from 1013.33 (SD = 1055.12) to 1578.67 (SD = 1354.09); the control group decreased from 1012.94 (SD = 1322.943) to 682.11 (SD = 754.89); having a stress goal significantly predicted a higher post-coaching positive affect and well-being, controlling the pre-score and other demographic factors: B = 0.37 and p < 0.05. Peer coaching showed a promising effect on improving PA and positive affect and well-being among college students.
Keywords: dept.hms; diet; mental health; peer-reviewed; physical activity; positive affect; sleep; stress

Discriminative ability of lower limb strength and power measures in lacrosse athletes - Talpey, Scott W.; Axtell, Robert; Gardner, Elizabeth; Maloney, Maggie; Newman, Thomas; Cordone, Jason; O’Grady, Mathew (International Journal of Sports Medicine, 2023)
The objective of this investigation was to compare isokinetic strength, countermovement jump and drop jump variables between high-contributors and low-contributors within NCAA Division I Men’s and Women’s lacrosse athletes. Men’s (N=36) and Women’s (N=30) NCAA Division I lacrosse athletes completed strength testing of the quadriceps and hamstring across three speeds (60°·s−1, 180°·s−1, 300°·s−1), countermovement and drop jumps. To determine the discriminative ability of select lower-limb strength and power characteristics participants were categorized as high-contributors (Males N=18, age=20.3±0.4 yrs, height=183.9±5.5 cm, mass=90.8±5.8 kg; Females N=15, age=20.8±0.8 yrs, height=169.3±6.7 cm, mass=64.1±7.2 kg) or low-contributors (Males N=18, age=19.5±0.2 yrs, height=184.1±5.6 cm; mass=87.9±8.1 kg; Females N=15, age=19.7±0.2 yrs, height=169.8±7.0 cm, mass=62.9±7.7 kg ) based upon the number of games the participants competed in during the regular season. Within the male cohort, moderate significant (p−1 (d=0.69) and peak power in countermovement jump (d=0.68). Within the women’s cohort a large (d=0.87) significant difference (p−1. Hamstring strength and lower-limb power are important strength measures for lacrosse performance and should be prioritized in training prescription for lacrosse athletes.
Keywords: Key words countermovement jump; dept.hms; drop jump; female athlete; peer-reviewed; performance